High-resolution micro-computed tomography reveals cracking in a hydrophobic composite; a new mechanism for mobilisation in controlled release applications. (March 2021) - Levett, Ian; Donose, Bogdan C.; Laycock, Bronwyn; Pratt, Steven
Abstract : High-resolution micro-computed tomography (μ-CT) provides new insights into the release of water-soluble crystalline materials from hydrophobic polymer matrices. This technique was applied to investigate the complex pathways underpinning the release of the agrichemical dicyandiamide (DCD), a common crystalline, water-soluble nitrification inhibitor, following its encapsulation in a biodegradable poly(3-hydroxybutyrate- co -3-hydroxyvalerate) (PHBV) matrix at a loading of 250 g kg −1 . Such a material allows controlled DCD delivery and improves its stability in tropical cropping systems. The insights gained from the use of this advanced 3-D imaging technique has led to a new understanding of the processes driving release of active agents and will aid the modelling and design of such tailored delivery formulations. These insights are broadly applicable and relevant to various soluble crystalline agrichemicals, drugs and medical implants. The release rate from DCD-PHBV pellets, fabricated through industrially relevant extrusion processing, was initially rapid, exponentially decaying over the first eight weeks. This was followed by a very gradual, linear release over the next 18 weeks. High-resolution μ-CT (0.5 μm) led to two important conclusions: i) the DCD that was rapidly mobilized existed within channels connected to the surface of the pellet, and ii) fine cracks present before and after release may explain the very slow mobilisation from the eighth week onward. Revealing the microstructure of this type of composite improves our current understanding of the mechanisms controlling the release of soluble crystalline materials encapsulated in a hydrophobic biodegradable polymer matrix. Graphical abstract: Image 1 Highlights: μ-CT reveals cracks that contribute to release of DCD from a biodegradable matrix. Analysis found 2–4 μm cracks that propagate from pores and vertices of DCD crystals. The biopolymer, PHBV, is shown to not follow Higuchi's classic moving front theory. Pore analysis quantifies initial and final porosity and orientation of DCD crystals.